(untitled) (Research, Society and Development, 2021)
Introduction: Covid-19 is defined as the respiratory infection caused by the SARS-CoV-2 coronavirus. The lack of specific treatments, the high incidence of the disease and the global concern with socioeconomic effects raise the need to determine prophylactic measures to combat this pandemic. Methodology: This is a systematic review, carried out based on research in Pubmed and DOAJ databases of works with the descriptors "prophylaxis" and "prevention" in Covid-19. The data were extracted in an Excel spreadsheet, organized by level of evidence and arranged in the classification “non-drug prophylaxis” and “drug prophylaxis”. The outcome considered was Covid-19 confirmed by the laboratory. The research provided 63 articles from the PubMed database and 388 results from the DOAJ database, with 19 papers selected. Non-pharmacological interventions, closing schools, mandatory community quarantine, mass testing with isolated cases, mandatory isolation of immigrants, social distance greater than 1 meter, use of disposable masks and hand hygiene significantly impact the peak, total amount of cases and duration of the outbreak, as well as the number of deaths. Screening of symptomatic patients in ports and airports has shown limited effectiveness. Of the pharmacological interventions, despite promising preclinical trials, current evidence does not support prophylactic use of vitamin D, zinc, chloroquine/hydroxychloroquine, ivermectin or colchicine in preventing Covid-19. Conclusion: The current pandemic is an unprecedented public and economic health crisis and the only effective forms of prophylaxis were non-medicated.